Dyslexia associated gene KIAA0319 regulates cell cycle during human neuroepithelial cell development - Paniagua, Steven; Cakir, Bilal; Hu, Yue; Kiral, Ferdi Ridvan; Tanaka, Yoshiaki; Xiang, Yangfei; Patterson, Benjamin; Gruen, Jeffrey R.; Park, In-Hyun (Frontiers in Cell and Developmental Biology, 2022)
Dyslexia, also known as reading disability, is defined as difficulty processing written language in individuals with normal intellectual capacity and educational opportunity. The prevalence of dyslexia is between 5 and 17%, and the heritability ranges from 44 to 75%. Genetic linkage analysis and association studies have identified several genes and regulatory elements linked to dyslexia and reading ability. However, their functions and molecular mechanisms are not well understood. Prominent among these is KIAA0319, encoded in the DYX2 locus of human chromosome 6p22. The association of KIAA0319 with reading performance has been replicated in independent studies and different languages. Rodent models suggest that kiaa0319 is involved in neuronal migration, but its role throughout the cortical development is largely unknown. In order to define the function of KIAA0319 in human cortical development, we applied the neural developmental model of a human embryonic stem cell. We knocked down KIAA0319 expression in hESCs and performed the cortical neuroectodermal differentiation. We found that neuroepithelial cell differentiation is one of the first stages of hESC differentiation that are affected by KIAA0319 knocked down could affect radial migration and thus differentiation into diverse neural populations at the cortical layers.